Designing Smart and Resilient Cities for a Post-Pandemic World Metropandemic Revolution - Larsson, Anthony (Routledge Advances in Regional Economics, Science and Policy, 2023)
Are pandemics the end of cities? Or, do they present an opportunity for us to reshape cities in ways making us even more innovative, successful and sustainable? Pandemics such as COVID-19 (and comparable disruptions) have caused intense debates over the future of cities. Through a series of investigative studies, Designing Smart and Resilient Cities for a Post-Pandemic World: Metropandemic Revolution seeks to critically discuss and compare different cases, innovations and approaches as to how cities can utilise nascent and future digital technology and/or new strategies in order to build stronger resilience to better tackle comparable large-scale pandemics and/or disruptions in the future. The authors identify ten separate societal areas where future digital technology can impact resilience. These are discussed in individual chapters. Each chapter concludes with a set of proposed "action points" based on the conclusions of each respective study. These serve as solid policy recommendations of what courses of action to take, to help increase the resilience in smart cities for each designated area. Securing resilience and cohesion between each area will bring about the metropandemic revolution. This book features a foreword by Nobel laureate Peter C. Doherty and an afterword by Professor of Urban Technologies, Carlo Ratti. It provides fresh and unique insights on smart cities and futures studies in a pandemic context, offers profound reflections on contemporary societal functions and the needs to build resilience and combines lessons learned from historical pandemics with possibilities offered by future technology.